MANAGEMENT STRATEGY OF ENDOWMENT FUNDS AND INCOME GENERATING UNITS (IGU) IN REALIZING FINANCIAL INDEPENDENCE OF ISLAMIC EDUCATIONAL INSTITUTIONS: AN ECONOMIC TRANSFORMATION ANALYSIS BASED ON ZISWAF - Ahmad Fikri; Herwina Bahar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study analyzes the strategic urgency of transforming the financing model of Islamic educational institutions in Indonesia from a traditional charity-based approach toward a sustainable social enterprise framework. Driven by structural fiscal limitations, sharp allocative disparities within public budgets (APBN/APBD), and the escalating commercialization of education, this research investigates the integration of public financing with Islamic Social Finance. Utilizing a qualitative-conceptual methodology with an economic and pedagogical approach, this paper evaluates the efficacy of an Integrated Islamic Social Finance (IISF) model and a Tiered Funding System. This system synthesizes productive waqf as a perpetual capital base, zakat as targeted tuition relief for marginalized students (dhuafa), and infak/sedekah as dynamic innovation funds. Furthermore, it explores the optimal deployment of institutional Income Generating Units (IGUs) alongside digital modernizations. The findings demonstrate that professionalizing asset management through mechanisms like Cash Waqf Linked Sukuk (CWLS) and establishing diversified sharia-compliant business units structurally insulates institutions from chronic dependence on student tuition fees, thereby fulfilling the dual mandate of teacher welfare and inclusive accessibility. Crucially, the adoption of digital technologies specifically Blockchain and Islamic Fintech emerges as an ethical and operational necessity under the Maqasid al-Shariah paradigm to safeguard public funds (Hifz al-Mal) via absolute, real-time transparency and automated, immutable auditing. This integrated model provides a robust conceptual blueprint for achieving long-term financial sovereignty, enhancing internal and external institutional efficiencies, and preserving the core socio-spiritual mission of Islamic education in the digital disruption era.